CoNiFe-layered double hydroxide decorated Co-N-C network as a robust bi-functional oxygen electrocatalyst for zinc-air batteries - Arafat, Yasir; Zhong, Yijun; Azhar, M.R.; Asif, M.; Tadé, Moses O.; Shao, Zongping (2023)
Rechargeable zinc-air batteries (ZABs) are cost-effective energy storage devices and display high-energy density. To realize high round-trip energy efficiency, it is critical to develop durable bi-functional air electrodes, presenting high catalytic activity towards oxygen evolution/reduction reactions together. Herein, we report a nanocomposite based on ternary CoNiFe-layered double hydroxides (LDH) and cobalt coordinated and N-doped porous carbon (Co-N-C) network, obtained by the in-situ growth of LDH over the surface of ZIF-67-derived 3D porous network. Co-N-C network contributes to the oxygen reduction reaction activity, while CoNiFe-LDH imparts to the oxygen evolution reaction activity. The rich active sites and enhanced electronic and mass transport properties stemmed from their unique architecture, culminated into outstanding bi-functional catalytic activity towards oxygen evolution/reduction in alkaline media. In ZABs, it displays a high peak power density of 228 mW cm−2 and a low voltage gap of 0.77 V over an ultra-long lifespan of 950 h. (Figure presented.).